Los censos visuales en transecto de banda subestiman la abundancia del pez león Pterois spp. en arrecifes coralinos del Caribe - Sabido-Itzá, Miguel Mateo; Castro-Pérez, José Manuel; Nava-Martínez, Gabriela; Medina-Quej, Alejandro; Hernández-Millán, Martha Beatriz (Revista de Biología Marina y Oceanografía, 2020)
The visual census of band transect (CVB) is one of the most used monitoring protocol on reefs, however this study confirms that its application fail in the detection and estimation of abundance of invasive lionfish. CVB vs Lionfish Search Census (CBP) was compared on Mexican Caribbean reefs. Differences in abundance of lionfish were found between CVB and CBP. Bias among both methods was significantly correlated to the cryptic behavior of inactivity and depth of the site. Finally, the use of different lionfish sampling methods and the application of CBP for monitoring reefs in the region are discussed.